2006
DOI: 10.1007/s00709-006-0159-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro microspore selection in maize anther culture with oxidative-stress stimulators

Abstract: In order to produce doubled-haploid maize plants tolerant of oxidative stress, in vitro microspore selection was carried out in anther culture with reactive oxygen species (ROS) progenitors such as paraquat, menadione, tert-butylhydroperoxide (t-BHP), and methionine combined with riboflavin. All the ROS progenitors reduced the anther induction, the formation of microspore-derived structures, and their regeneration potential. Abnormal cell divisions and progeny cell degradation could be observed during the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…To conclude, the plant‐specific glutaredoxins ROXY1 and ROXY2 require a conserved glycine interacting with GSH for modification of target proteins. Environmental stress is known to decrease plant fertility, and gametophyte development is highly sensitive to stress and reactive oxygen species (Ambrus et al. , 2006; Sun et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude, the plant‐specific glutaredoxins ROXY1 and ROXY2 require a conserved glycine interacting with GSH for modification of target proteins. Environmental stress is known to decrease plant fertility, and gametophyte development is highly sensitive to stress and reactive oxygen species (Ambrus et al. , 2006; Sun et al.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, the plant-specific glutaredoxins ROXY1 and ROXY2 require a conserved glycine interacting with GSH for modification of target proteins. Environmental stress is known to decrease plant fertility, and gametophyte development is highly sensitive to stress and reactive oxygen species (Ambrus et al, 2006;Sun et al, 2004). Mutagenesis studies have suggested that conserved cysteines in MYB R2R3 proteins mediate their redox-dependent ability to bind to promoter sequences (Heine et al, 2004), and thus these proteins might represent targets for post-translational modification by ROXY1 and ROXY2.…”
Section: A Model For Roxy1/2 Function In Anther Developmentmentioning
confidence: 99%
“…In a cytoplasmic male sterile line of rice the oxidative stress originating in mitochondria was found to be associated with premature abortion of microspores in the early stage of pollen development [34]. As well, the treatment of maize anthers with the ROS progenitors resulted in abnormal cell divisions and progeny cell degradation during the development of the microspores [35]. Similarly, the development of fertilized egg to an embryo has been found to be sensitive to a multitude of environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…We compared two cultivation methods using two culture media N6 (Chu 1981) and YP in our experiments. N6 and YP media are the most often used media for microspore initiation in maize anther culture (Ting et al 1981;Genovesi and Collins 1982;Petolino and Jones 1986;Tsay et al 1986;Petolino et al 1988;Barloy et al 1989;Büter et al 1993;Barnabás et al 1999;Nageli et al 1999;Aulinger et al 2003;Jäger et al 2005;Ambrus et al 2006;Pret'ová et al 2006). A direct comparison of both media has not been performed yet.…”
Section: Discussionmentioning
confidence: 97%